Transformed by praise the purpose and message of the Psalms - Futado, Mark David (Phillipsburg, NJ Presbyterian and Reformed, 2002)
Includes bibliographical references and index.
Keywords: Bible. O.T. Psalms -- criticism, interpretation, etc